Fenomena Gegar Budaya dalam Komunikasi Lintas Budaya: Studi pada Mahasiswa Indonesia di University of Queensland - Azzahra, Sydney; Djaya, Khairunnisa; Puspitasari, Citra Siamy (Syntax Literate, 2025)
Indonesia is ranked 22nd in the world as the country with the most sending students abroad. Based on a study by the Indonesian International Education Consultant Association organization, there are more than 35,000 Indonesian students who study abroad each year, Australia is the most popular destination country for Indonesian students. Of the many choices of universities in Australia, according to the Times Higher Education University of Queensland, the university that has the most Indonesian students in Australia has the highest world ranking in Australia. Studying abroad, which sounds like fun, also has various obstacles. Culture shock in intercultural communication is one of the obstacles. This obstacle can also cause anxiety or even depression. This study describes the Cultural Concussion Phenomenon in Intercultural Communication experienced by Indonesian students who are continuing their studies at the University of Queensland. This study refers to the Developmental Model of Intercultural Sensitivity (DMIS) model with a phenomenological qualitative method. The research was carried out by conducting observations, in-depth interviews with three Indonesian students who were continuing their studies at the University of Queensland. This study aims to determine the stages of culture shock Intercultural communication faced by Indonesian students who are continuing their studies at the University of Queensland. The results of the study show the stages of culture shock in Intercultural communication faced by students from Indonesia who continue their studies at the University of Queensland.